PENGARUH DISCOVERY LEARNING BERBASIS DEMONSTRASI TERHADAP PARTISIPASI DAN HASIL BELAJAR SISWA SMP - Maimunawarah Maimunawarah; Nuril Huda; Sri Utami (Universitas HKBP Nommensen, 2026)
This study aims to evaluate the effect of the Discovery Learning model, demonstrated through the demonstration method, on students’ participation and science learning outcomes in grade VII at SMPN 3 Camplong. The main problem addressed is the low level of student engagement and learning achievement. The research employed a one-group pretest–posttest design involving 30 students. Data were collected through observation and tests. The results indicate a significant improvement in both variables. Learning participation increased from 59.17 to 77.83, with paired sample t-test results of t = –13.214 and p = 0.000. Learning outcomes improved from 57.90 to 79.17, with a t-value of –15.002 and a p-value of 0.000. These findings confirm that the implementation of demonstration-based Discovery Learning effectively enhances students’ active involvement and improves their understanding of science concepts. This model is recommended as an effective alternative teaching strategy at the junior high school level. The novelty of this research lies in the analysis of the influence of Discovery Learning Based on Demonstration on Students' Participation and Learning Outcomes, which is still rarely done. This research implies that the application of a learning model that combines discovery activities with real demonstrations can increase student active involvement while strengthening conceptual understanding.